Analisis Kandungan Natrium (Na) pada Tanaman Porang (Amorphophallus Oncophyllus) - Sahputra, Rachmat (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Abstract: The nutritional content contained in the porang plant, as is the case with other root crops, also contains carbohydrates, contains fat, protein, minerals, vitamins and fiber. This study aims to obtain data on the average sodium mineral content in Porang plants. The analytical method uses an atomic absorption spectrometer (AAS) in flame emission mode. Sample solutions containing sodium were stored in polyethylene bottles. Sodium has a maximum light emission at a wavelength of 589 nm, where the working procedure is that the sample is nebulized into a gas flame to allow controlled excitation to occur. The sodium resonance spectral line at 589 nm is isolated with an interference filter or with a light dispersing device such as a prism or grating. The intensity of the emitted light is measured with a photomultiplier, or photodiode. The intensity of light at 589 nm will be roughly proportional to the concentration of sodium. From the results of the analysis using the AAS method, it was found that the sodium content in the porang tuber sample was obtained from Nganjuk district, East Java, with a sodium content of 51.25 mg per 1 kg of porang tuber flour or 5.125 mg sodium per 100 g of porang tuber. This content is lower than the sodium content in corn, but higher than the sodium content in rice.Keywords: Analysis of sodium content, porang plantsAbstrak: Kandungan nutrisi yang terdapat di dalam tanaman porang, seperti halnya dengan tanaman umbi-umbian lain juga mengandung karbohidrat, lemak, protein, mineral, vitamin dan serat. Penelitian ini bertujuan untuk mendapatkan data kandungan mineral natrium rata-rata pada tanaman porang. Metoda analisa menggunakan spektrometer serapan atom (AAS) dalam mode emisi nyala. Larutan sampel yang mengandung natrium disimpan dalam botol polietilen. Natrium memiliki cahaya emisi maksimum pada panjang gelombang 589 nm di mana prosedur kerjanya sampel dinebulisasi menjadi nyala gas agar terjadi eksitasi yang dikontrol dengan garis spektrum resonansi natrium pada 589 nm diisolasi dengan filter interferensi atau dengan perangkat pendispersi cahaya seperti prisma atau kisi-kisi. Intensitas cahaya emisi diukur dengan photomultiplier, atau photodiode. Intensitas cahaya pada 589 nm kira-kira akan sebanding dengan konsentrasi Natrium. Dari hasil analisis melalui metoda AAS diperoleh kandungan Natrium dalam sampel umbi porang yang diperoleh dari kabupaten Nganjuk Jawa timur dengan kandungan natrium sebesar 51,25 mg per 1 kg tepung umbi porang atau 5,125 mg natrium per 100g umbi porang. Kandungan ini lebih rendah dibanding kadar Natrium di dalam jagung, tetapi lebih tinggi dari pada kandungan natrium dalam beras.Kata-kata kunci: Analisis kandungan natrium, tanaman porang